TANGGUNGJAWAB PENGUSAHA PELAYARAN DALAM PERJANJIAN KERJA LAUT (PKL) TERKAIT DENGAN JAM KERJA - Agustina Balik (SASI, 2016)
The role of the Sea Working Agreement is very important as a legal umbrella thatprotects the crew. By not including the clause on working hours in the Sea Work Agreement,sometimes the crew may work beyond the prescribed hours of work even if their breaks arereduced if at that time there is urgent work to be done and can not be abandoned. Likewise onholidays every week or official holidays they never enjoy. This has an impact on wagepayments that are inconsistent with working hours and over-hours of crew work. The research method used is normative legal research method to study the aspect ofresponsibility of shipping businessman to Sea Working Agreement which is expected toprovide guarantee of Legal Protection for crew related to working hours. The responsibility ofthe shipping businessman is to make a Sea Working Agreement in accordance with theprovisions of articles 399 and 400 of the Criminal Code, subject to Article 401 KUHD inrelation to the contents of the Sea Work Agreement. Implementation of this responsibility willcreate legal protection for the crew of the vessel in respect of the wages they receive inaccordance with the imposition of working hours specified in Government Regulation Number7 of 2000 on Marine Affairs. Syahbandar must be proactive in paying attention to the makingof the Sea Working Agreement, by reviewing and analyzing the existing clauses so that therights of the crew may be clearly stated in the Sea Working Agreement.